ISOLATION AND CHARACTERIZATION OF LOCAL ROOT-NODULE BACTERIAL STRAINS OF MEDICINAL LEGUMINOUS PLANTS IN THE ALA-ARCHA GORGE (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This work presents an expanded review of modern studies devoted to the diversity and biotechnological potential of root-nodule bacteria (Rhizobium spp., Bradyrhizobium spp.) associated with medicinal leguminous crops. Special attention is given to the ecological conditions of the high-altitude Ala-Archa Gorge, where environmental stress factors create specific requirements for the adaptive capacity of symbiotic bacteria. Methods of isolation, identification, and evaluation of the symbiotic efficiency of rhizobia described in the scientific literature are summarized. An analytical systematization of published data on the effects of inoculation on plant growth (clover, lupine) is provided.
Keywords: Nodule bacteria, rhizobia, medicinal legumes, symbiosis, nitrogen fixation, clover, lupin, strain isolation, inoculation